Mary as the End of Popular Contemplation (Teología, 2023)
In Latin America, especially the simple people, learned to see the Virgin together with God, forming part of the divine complex that gives life its ultimate meaning. Hence it is addressed to Mary as the end, by command and gift of Christ: “Thereyou have your Mother”. A re-evaluation of the vital perception of the sensus fidei, which is a gift of the Holy Spirit, can help us to ponder more adequately the richness of direct apprehension, which is always greater than that of reflexive conceptual expression. In this sense, the sensus fidei is one of the factors in the development of Christian doctrine, which cannot be explained by having recourse exclusively to the model of deductive reasoning by which other truths are deduced from certain given truths. The impulse that promotes this trans-conceptualization has its source in the intuitive perception of the validity of the formulas that emerge in the conceptual schemes of various cultures, and give rise to the acquisition of new categories that allow a reformulation of the tradition and a progress in dogmatic development. Hence the importance in the vocation of the theologian to a conceptualization of this pre-conceptual apprehension that the diversification of the theological life of Christians is capable of arousing. Above all, if, instead of resystematizing what is already systematized, he is capable of becoming attentive to  the expressions that the sensus fidei always has to offer to the authentic progressof the tradition.